Everday Life in a Soviet Factory: The Case of ELFA Radio Factory in the 1960s and 1980s - Mikalajūnaitė, Ieva (Vilnius University Open Series, 2024)
This study takes a closer look at how Soviet workers lived and adapted to the changes, reconciling personal ambitions with the economic and ideological plan. The everyday life is examined in terms of the worker’s relationship to the factory and its role in the worker’s life. This study analyses the effects of the deficit economy, speculation and the plundering of socialist property, which contributed to everyday life. This study reveals what the realisation of socialist ideals, plans and visions looked like through the eyes of an ordinary worker at the “Elfa” radio factory, focusing on the everyday life of the workers, revealing the real experiences of the people who worked in the factory.
Keywords: “Elfa” factory; workers; industrialization; socialist ideology; daily life; disciplinary penalties; ideology; socialism